COMPREHENSIVE THEORETICAL STUDY: IMPLICATIONS OF DRUG ABUSE AND PREVENTION AND OVERCOME STRATEGIES - Ade Onny Siagian; Nurhidayati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
A theoretical review of the abuse of narcotics, alcohol, psychotropic substances, and other addictive substances (NAPZA) is a complex global problem with multidimensional implications, encompassing health, psychological, social, and economic aspects. This study aims to present a comprehensive theoretical review by reviewing key literature to identify in-depth the main implications of NAPZA abuse and evaluate the effectiveness of developed prevention and response strategies. The results of the review indicate that the implications of NAPZA are not limited to individual physical and mental damage (such as impaired cognitive function, depression, and the risk of infectious diseases), but also exacerbate family dysfunction and increase the socio-economic burden on the country. In the context of response, this study highlights a shift in focus from a retributive approach to an integrated multidisciplinary approach. Effective prevention strategies emphasize school- and family-based interventions, strengthening self-resilience, and relevant educational campaigns. Meanwhile, response emphasizes a rehabilitation model that combines medical therapy, psychosocial therapy, and social reintegration. This research provides a strong theoretical foundation for policy makers, health practitioners, and educators in formulating more adaptive and evidence-based intervention programs to address the challenges of drug abuse today.